Fibrosis progression in interferon treatment-naive Chinese plasma donors with chronic hepatitis C for 20 years: a cohort study - Jun-Feng Li (International Journal of Infectious Diseases, 2014)
Objectives: To evaluate the progression of fibrosis and factors influencing this in interferon (IFN) treatment-naive Chinese plasma donors infected with hepatitis C virus (HCV) for approximately 20 years. Methods: From July 2010 to June 2011, we investigated 122 IFN treatment-naive chronic hepatitis C (CHC) patients infected by plasma donation in 1992–1995. Liver fibrosis stage and inflammation grade were evaluated by Metavir and Scheuer scoring systems, respectively. Results: One hundred and twenty patients underwent liver biopsy. Liver biopsy was not performed in one patient with cirrhosis due to ascites, and another patient was excluded because of an invalid biopsy specimen. Cirrhosis was observed in three patients (fibrosis stage F4 in two patients revealed by biopsy, and one patient with ascites confirmed by physical and Doppler ultrasound examination). Fibrosis stages F1 and F2 were present in 55 and 50 patients, respectively. The severity of liver inflammation was independently related to moderate to severe fibrosis (F ≥2). Older age and male sex showed an increasing tendency for more severe fibrosis (F3/F4) in the present cohort. Conclusions: Based on histopathology results, the progression of fibrosis in patients with CHC infected by repeated plasma donation is slow after HCV infection of approximately 20 years. Liver inflammation is closely related to the development of moderate to severe liver fibrosis.